ANTIBACTERIAL ACTIVITY OF EXTRACTS OF LEAVES OF LEILEM (Clerodendrum minahassae Teijsm. & Binn.) ON GROWTH GRAM - POSITIVE BACTERIA Staphylococcus aureus strains ATCC 25923 - Jefry Oldy Raturandang; Dintje Pendong; Masje Wurarah (Indonesian Biodiversity Journal, 2021)
Leaf leilem (Clerodendrum minahassae Teism. & Binn.) commonly used by the Minahasa as food and traditional medicine for treating intestinal worms, abdominal pain, and pain in the chest. Gram-positive bacteria Staphylococcus aureus ATCC 25923 strain is a type of bacteria that is found in humans and can be the cause of the emergence of the disease. This research aims to know the types of solvents are most effective and how the antibacterial activity of extracts of leaves of leilem on the growth of the bacteria Staphylococcus aureus strains ATCC 25923. The solvent used is ethanol is polar, ethyl acetate which is semi polar, and n-heksan which is non polar. Preliminary research has been conducted on konsenterasi extract with 100 ppm 200 ppm 400 ppm and 800 ppm, the antibacterial activity of the most optimal at 800 ppm so the data will be used for the analysis in this study was konsenterasi 800 ppm. Deuteronomy was done by as much as 3 times. Positive control using antibiotics clindamicyn 400 ppm and negative controls using aquades and 10% DMSO. Isolation of bacteria using scratch in zig-zag and to test the antibacterial activity of using diffusion well in order. Results of the study showed that the percentage yield of solvent is ethanol that is 1,2329% in maceration 1:4. Drag the diameter of most bacteria are grown on ethyl acetate extract polar spring with a grade average of 12.6 mm. Based on the analysis of OneWay ANOVA showed different results for real then followed by Tukey test, to see that these three types of different extract significantly in inhibiting the growth of gram positive bacteria Staphylococcus aureus strains ATCC 25923. In conclusion, namely the first ethanol is a solvent that is most effective in dissolving the leaves leilem, both of the antibacterial activity in sequence from the most minor to the most massive is the n-heksan (non-polar), ethanol (polar), and ethyl acetate (semi polar). The third conclusion in the optimum konsenterasi 800 ppm, extract n-heksan n-heksan (non-polar), ethanol (polar), and ethyl acetate (semi polar) showed antibacterial activity significantly different.